Implementing a Value Co-creation Network: Some Lessons from Taiwan's Steel Industry. Issue 1 (2nd January 2021) - Fang, Shih-Chieh; Chen, Ching-Hui; Yang, Chen-Wei
ABSTRACT: This practitioner note is to combine transaction cost theory and the knowledge-based view of the firm to investigate why and how the hub company in a network coordinates its members to co-create value in the steel industry. A theoretical model was proposed. A qualitative case study based on original survey data in the context of Taiwan's steel industry. The analyses are based on different types of data: (1) direct observations, (2) semi-structured interviews, and (3) archived material. First, participant observation was employed since to analyze the organizational behavior and cooperation patterns among the members of the steel collaborative network. Second, we interviewed several managers, researchers, and scholars and kept records of all our data, and developed a list of codes to analyze the interviews' transcripts by using the constructs obtained by the primary theoretical framework. After coding, pattern-matching techniques and explanation building techniques were used for analyzing data across informers and matching the information in the theoretical framework. Pattern-matching technique can classify open-ended comments into generalized classifications and evaluate the prompted comments regarding a proposition. We compared the different cases by examining new classifications and responses. The explanation building facilitated a preliminary assessment of the presumed set of causal link to improve the tentative theoretical framework and help develop preliminary propositions . Except one new construct emerging, the findings suggest preliminary evidence that the network's value co-creation practices in steel collaborative network influenced by transaction cost factors and knowledge-based factors as theory argued. Two propositions are induced from the qualitative data. Proposition 1: The level of transaction cost factors perceived by ERC members is positively related to the degree of implementation of network's value co-creation practices in Taiwan's steel industry. Proposition 2: The level of knowledge-based factors perceived by ERC members positively related to the degree of implementation of network's value co-creation practices in Taiwan's steel industry. Theoretical implications contribute to strategic technology management research by providing a conceptual model for describing and assessing a steel collaborative network's implementing process for value co-creation by using a case approach. Researchers have begun exploring inter-organizational knowledge creation in the steel industry and provided significant support to the prominence of new steel product-services knowledge. However, only a few studies focused on why and how the value of new steel product-services knowledge is co-generated within a steel collaborative network, and empirical evidence is lacking. Hence, it is important to develop a value co-creation model for steel collaborative networks to identify the determinants and procedure of value co-creation by integrating the knowledge-based view of the firm and transaction cost theory. This approach may help clarify the motivations of various strategic network value co-creation activities in the steel industry, especially the integration of complementing logics of transaction cost theory and knowledge-based view. Moreover, this practitioner note used qualitative research to contextualize the value co-creation network, and, thus, helps extend value co-creation theories with respect to the steel industry, which have been criticized for their unclear management mechanisms. Results also contribute to the findings of Marcos-Cuevas et al. (2016 ) and add appropriating as a sub-construct of the network's value co-creation practices. Regarding business marketing implications, the proposed theoretical framework has several implications for marketing managers in companies operating within steel collaborative networks. Understanding the strategic model of network's value co-creation practices may assist a hub steel company's administrators to adopt effective marketing strategies for co-generating innovative value and identifying both knowledge-based factors and transaction cost factors that may impede the co-creation of value in the network context. Hence, this framework contributes to a better understanding of how networks can be managed to improve value co-creation practices and also provides a practical way of managing value co-creating networks. Rather than managing a discrete set of alliances, steel network members need to collaborate to implement linking, materializing, institutionalizing, and appropriating to minimize the unintentional outflow of assets to possible challengers. This approach would also support the effective transfer of knowledge-based resources for value co-creation within their network. Although growing attention in practices of value co-creation, an over-emphasizing on traditional supplier-customer co-operation has limited our thinking of where and how network-level value co-creation can initiate and how it is implemented. In Taiwan's steel industrial context, the model proposes an implementation process of value-co-creation by Steel Collaborative Network-ERC that comprise of steel suppliers, universities, research institutes, and customers. It demonstrates the impact of the steel collaborative network's value co-creation determinants on its value co-creation practice and the way steel collaborative networks co-create their value. Steel Collaborative Network's value co-creation practices are relied on both the transaction cost factors and knowledge-based factors in Taiwan's steel industry.